Rice policy, trade, and exchange rate changes in Indonesia: a general equilibrium analysis - Robinson, Sherman; El-Said, Moataz; San, Nu Nu (International Food Policy Research Institute, 1998)
This paper presents an agriculture-focused computable general equilibrium model that can be used to analyze the economy-wide impacts of changes in technology, market structure, and the foreign exchange rate on resource allocation, production, and trade in Indonesia. The model includes a specification of the rice market and the government price-support, stocking, and trade policies for rice. Using a mixed complementarity approach, the model incorporates inequalities and changes in policy regime as prices and/or stocks move within specified bands. The model is used to examine the impact on the Indonesian economy of changes in rice yield and exchange rates given different assumptions about the operations of BULOG (National Logistic Agency). An important result is that there is inefficient allocation of resources within agriculture and the rest of the economy if BULOG operates to maintain the rice price when there are significant increases in rice productivity or changes in the exchange rate. With increased productivity in rice, the price support scheme retains resources in rice production that would be better used in other, high value, agriculture. With devaluation, maintaining a low rice price discriminates against rice producers and hence slows the process of structural adjustment. In addition, the price support program is costly and strains the government accounts, even if the administrative costs of operating the program are ignored.